Men Who Know They Are Watched: Some Benefits and Costs of Jailing for Nonpayment of Support - Chambers, David L. (1977)
Suppose that by some mysterious process the police in your town received each Monday a list of all the robberies and burglaries committed during the preceding week and the names of the persons who committed them. Suppose further that the list itself was admissible in evidence at trial and generally led to conviction. And suppose finally that persons considering committing offenses knew that the police had such a list and used it, relentlessly tracking down the miscreants named on it. Under such circumstances, one would probably expect that many potential offenders in the town with the magical list would resist the temptation to rob or burgle stores